Evaluation of suitable chlorine bulk-decay models for water distribution systems - Fisher, I.; Kastl, G.; Sathasivan, Arumugam (IWA Publishing, 2011)
Maintaining the chlorine residual is a major disinfection goal for many water distribution systems. A suitable general chlorine bulk-decay model is required for simulation of chlorine profiles in networks to assist disinfection planning/management efficiently. The firstorder model is unsuitable due to inaccuracy and inability to represent rechlorination. Three potentially suitable, simple, reactant models were compared. The single-reactantmodel was found to be unsuitable, as it was inaccurate when restricted to using a single set of invariant parameters. The two-reactant model was more suitable than the variablerate-coefficient model, although both models were accurate under the same restriction. The two-reactant model was then calibrated against datasets consisting of multiple decay tests for five distinctly different waters. It accurately predicted data reserved for validationover the chlorine concentration range of 0e6 mg/L, using a single set of invariant parameters, and is therefore the simplest, generally suitable model for simulating chlorine profiles in distribution system networks.